Esthetic composite restoration - A. Fetsych (LLC "Endo Press", 2020)
Perfect anterior restoration acts as an advertisement for the skills of the dental professional. Most interventions in anterior maxilla are accomplished with the direct placement of composite resins. The skill of the dentist to achieve a natural anatomical shape and color match with the adjacent teeth are prerequisites to achieving a pleasing esthetic result, which can also be assessed easily by the patients. This case report describes minimally invasive restoration of the tooth trauma during the orthodontics using stratfTcation technique.